Dinamika Ketimpangan Ekonomi Provinsi-Provinsi di Pulau Sumatera Tahun 2020-2024 - Hidayat, Muhammad Rizky; Hasmarini, Maulidyah Indira (Community Engagement and Emergence Journal (CEEJ), 2025)
This research effort conducts a comprehensive analysis of the determinants affecting income inequality in Provinces in Sumatra Island during the period 2020 to 2024, using the Ordinary Least Squares (OLS) methodology. The variables examined include Gross Regional Domestic Product (GRDP), number of educational institutions, domestic capital investment and the level of the consumer price index. The findings show that domestic investment and GRDP have a positive and statistically significant impact on income inequality, indicating that financial investment is concentrated in certain regions exacerbating economic disparities. In contrast, the consumer price index shows a substantive negative effect on inequality, implying that an increase in the consumer price index can contribute to reducing disparities through a redistributive mechanism that benefits low-income demographics. Meanwhile, the number of educational institutions does not show a significant effect on income inequality. The analytical model explains 42.61% of the variance in income inequality in 8 Provinces in Sumatra Island. These findings underscore the critical need to equalize the distribution of investment, improve the quality of education, and maintain a stable level of the consumer price index to encourage more inclusive economic growth.